Cosmological Redshift Drift - Jaminy, Sanatan (IISER Mohali, 2024)
The interpretation of most of our cosmological observables is model-dependent. In this regard, Cosmological Redshift drift measurements provide a unique Cosmological probe in the sense that it is a model-independent variable. Herein, we first describe how the phenomenon of redshift arises, and then go on to develop a completely model-independent mathematical description of Cosmological Redshift Drift. We discuss how peculiar veloc- ities and other perturbations might affect drift measurements. Then we go on to see how redshift drift can provide a framework to provide constraints on the parameters of modi- fied theories of gravity. In the end, we also briefly discuss the feasibility of redshift drift measurements.
under embargo period
Keywords: Cosmology; Redshift